IMPROVEMENT OF ABILITY TO SOLVE STORY PROBLEM ON FRACTIONS THROUGH THE APPLICATION OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE - Venny Noermalita Sari; Siti Kamsiyati; Muhammad Shaifuddin (Universitas Sebelas Maret, 2018)
The purpose of this research to improve of ability to solve story problems on fractions through the application of cooperative learning model type Think Pair Share. CAR takes place in two cycles, each cycle consists of 2 meetings and 4 stages. The subjects of this research are classroom teachers and students of 5th Grade Student’s of Banyuagung 2 Primary School Number 159 Surakarta in academic year of 2017/2018. The data collecting technique are observation, interview, test, and documentation. Validity test of this research are content validity, source triangulation, and technique triangulation. The data analysis techniques used in this research are comparative descriptive technique, critical analysis, and interactive analysis model from Miles & Hubberman. The conclusion of this research that is the application of cooperative learning model type Think Pair Share could increase the ability to solve story problems on fractions.